2019
DOI: 10.1155/2019/9796735
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Serum Matrix Metalloproteinase- (MMP-) 3 Levels and Systemic Lupus Erythematosus: A Meta-analysis

Abstract: Introduction. Matrix metalloproteinase (MMP) is an emerging disease marker in rheumatic diseases. This is a meta-analysis aimed at systematically reviewing association between serum MMP-3 levels and systematic lupus erythematosus (SLE) activity, which sought to raise interest in MMP-3 as a putative biomarker. Methods. We conducted a meta-analysis of serum MMP-3 levels in patients with SLE and controls. We performed a PubMed search, EMBASE search, and forward search of the retrieved articles published until Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…HDQ interferes with the stimulatory effect of platelet aggregation even in the presence of a thrombin agonist [263]. MMPs are matrix metalloproteinases which are enzymes involved in extracellular matrix remodeling, and TIMPs are counter regulatory tissue inhibitors of MMPs [184,264] that have been extensively studied in SLE [185,265]. Research has shown that HDQ modulated MMPs-TIMPs interaction assisting in maintaining homeostasis of the extracellular matrix [266,267] and may thus play a role in reducing NETs.…”
Section: Nadph/ros Inhibitors and Netsmentioning
confidence: 99%
“…HDQ interferes with the stimulatory effect of platelet aggregation even in the presence of a thrombin agonist [263]. MMPs are matrix metalloproteinases which are enzymes involved in extracellular matrix remodeling, and TIMPs are counter regulatory tissue inhibitors of MMPs [184,264] that have been extensively studied in SLE [185,265]. Research has shown that HDQ modulated MMPs-TIMPs interaction assisting in maintaining homeostasis of the extracellular matrix [266,267] and may thus play a role in reducing NETs.…”
Section: Nadph/ros Inhibitors and Netsmentioning
confidence: 99%
“…Despite the pathogenesis of SLE still not being entirely understood, investigations have pointed out its connection with deregulated MMPs [ 30 ]. In specific, Gelatinase B/MMP-9 involvement in SLE as a dangerous or advantageous molecule is still debatable because of contradictions in the published studies.…”
Section: Discussionmentioning
confidence: 99%
“…MMP8 is believed to be one of the key regulators of tissue degradation and remodeling, which plays a central role in various important processes such as morphogenesis, tissue repair, wound healing and remodeling, in response to injury [41]. Various MMPs like MMP-2, MMP-3, and MMP-9 elevated level is reported for RA and SLE [27,42,43]. NFIL3 (E4BP4) is an important human transcription factor in autoimmune response, the over-expression of which leads to the downregulation of autoimmune responses in SLE patients via inhibiting the expression of CD40L [44] mutations in this gene can alter the immune hypothesis and sensitize for arthritis pathology [28].…”
Section: Discussionmentioning
confidence: 99%